Thực hành trách nhiệm xã hội, danh tiếng và tài sản thương hiệu của các trường đại học công lập tại Việt Nam - Bùi Hữu, Đức; Bùi Khánh, Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The paper studies the relationship between university social responsibility (USR), reputation, and brand equity of universities. Using structural equation modeling method on a research sample of 361 students and alumni of Vietnamese public universities, the findings indicate that two types of USR for learners and for community have direct positive impacts on the university's reputation. Besides, they have also full mediating impact, through the reputation, on brand equity of Vietnamese public universities. In contrast, USR for employees does not have a significant impact on university reputation and brand equity. The research results also confirm the positive impact of reputation on brand equity of Vietnamese public universities.
Keywords: Social Responsibility; University Reputation; Brand Equity; Public University; Vietnam